2019
DOI: 10.1371/journal.pone.0213406
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical classification of adolescent idiopathic scoliosis: Identifying the distinguishing features in 3D spinal deformities

Abstract: This study aimed to identify the differentiating parameters of the spinal curves’ 2D projections through a hierarchical classification of the 3D spinal curve in adolescent idiopathic scoliosis (AIS). A total number of 103 right thoracic left lumbar pre-operative AIS patients were included retrospectively and consecutively. A total number of 20 non-scoliotic adolescents were included as the control group. All patients had biplanar X-rays and 3D reconstructions of the spine. The 3D spinal curve was calculated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 35 publications
1
45
0
1
Order By: Relevance
“…This centerline was isotropically normalized in a way that all the spines have the same heights while modifying the antero-posterior and lateral coordinates by the same factor. The reliability of this method in evaluating the 3D spinal curves was shown previously [3,15].…”
Section: Subjectsmentioning
confidence: 74%
See 4 more Smart Citations
“…This centerline was isotropically normalized in a way that all the spines have the same heights while modifying the antero-posterior and lateral coordinates by the same factor. The reliability of this method in evaluating the 3D spinal curves was shown previously [3,15].…”
Section: Subjectsmentioning
confidence: 74%
“…As shown previously, the axial projection of the curve carries important information for surgical and non-surgical management of the right thoracic AIS [6,[8][9][10]. It was also shown that the sagittal profile strongly relate to the patterns of axial deformation using mechanics of deformation in an elastic rod [3,11,12]. Here, it is studied if the axial projection of the curve varies within the Lenke types and whether that variation relates to the sagittal curvature of the spines within these subtypes.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations